Starting at Birth: An Integrative, State-of-the-Science Framework for Optimizing Infant Neuromotor Health - Peyton, Colleen; Sukal Moulton, Theresa; Carroll, Allison J.; Anderson, Erica; Brozek, Alexandra; Davis, Matthew M.; Horowitz, Jessica; Jayaraman, Arun; O'Brien, Megan; Patrick, Cheryl; Pouppirt, Nicole; Villamar, Juan; et al. (Frontiers in Pediatrics, 2022)
Numerous conditions and circumstances place infants at risk for poor neuromotor health, yet many are unable to receive treatment until a definitive diagnosis is made, sometimes several years later. In this integrative perspective, we describe an extensive team science effort to develop a transdiagnostic approach to neuromotor health interventions designed to leverage the heightened neuroplasticity of the first year of life. We undertook the following processes: (1) conducted a review of the literature to extract common principles and strategies underlying effective neuromotor health interventions; (2) hosted a series of expert scientific exchange panels to discuss common principles, as well as practical considerations and/or lessons learned from application in the field; and (3) gathered feedback and input from diverse stakeholders including infant caregivers and healthcare providers. The resultant framework was a pragmatic, evidence-based, transdiagnostic approach to optimize neuromotor health for high-risk children based on four principles: (a) active learning, (b) environmental enrichment, (c) caregiver engagement, and (d) strength-based approaches. In this perspective paper, we delineate these principles and their potential applications. Innovations include: engagement of multiple caregivers as critical drivers of the intervention; promoting neuromotor health in the vulnerability phase, rather than waiting to treat neuromotor disease; integrating best practices from adjacent fields; and employing a strengths-based approach. This framework holds promise for implementation as it is scalable, pragmatic, and holistically addresses both the needs of the infant and their family.